Design activism: catalysing communities of practice. Issue 2 (June 2020) - Mallo, Daniel; Tardiveau, Armelle; Parsons, Rorie
Abstract : Over the last decade, we have witnessed renewed interest in design as a socially engaged practice. Much of the debates around 'social design' point towards myriad approaches and disciplinary fields interwoven with grass-roots initiatives and social movements. Among these, design activism has gained traction as critical spatial practice that operates on the fringes of commercial and institutional spheres. The temporal, spatial and experimental nature of design activism is well delineated in scholarship but its long-term effect on everyday urban environments remains elusive. Moreover, the influence of design activism on socio-spatial dynamics is indeed largely under researched. By mobilising social practice theory, this paper proposes a novel theorisation of design activism that sheds light on the social formations and collective practices catalysed through the activist impulse. This ontological shift embraces an understanding of the socio-material world through practice. Such characterisation of design activism underscores collective moments of integration of the constitutive elements of practice, encapsulated by Shove, Pantzar and Watson as 'material, competence and meaning'. The authors' own empirical research, funded by the Economic and Social Research Council (ESRC) in the UK, reveals design activism as necessarily intertwined with other everyday practices – gardening, celebrating, playing – that coalesce around a shared sense of citizenship. It also advances the role of design activism in forging communities of practice: mutually supportive and self-sustaining groups emerging out of the personal relations sustained and organised around a practice of place making.